SIMULASI TWO LEVEL BOOST DC DC CONVERTER MENGGUNAKANSOFTWARE MATLAB SIMULINK - Muhammad Wildan Nashrullah; Mochammad Rusli; n/a Rahmadwati (Jurnal Mahasiswa TEUB, 2023)
Two level boost dc dc converter is a converter which has the advantage of being more economical if used in voltage increases in a large range. This research begins with data testing using MATLAB software, and emphasises the simulation by paying more attention to the parameters to adopt output voltage variations. Mathematical models in a physical system can be obtained in two ways, namely through analytical and experimental approaches. To obtain a system model is by using equations from the laws of physics and the components contained in the system. This research aims to boosting voltage in two level boost DC DC converter using Matlab simulink software. The method used in this research is a method with an experimental approach or identification method is the formation of a mathematical model of a physical system based on observation data by recording every relation of input and output data from a physical system. Then the data pairs are calculated with an algorithm from the identification method so that a mathematical equation that can represent the actual physical system will be obtained. Variations of conditions used in this analysis include changes in power supply of 250V, 360 Ω resistor, 4.5573.10-4 H inductor and 1.4583.10-6 F capacitor, and 16.67% duty cycle. The results obtained in this study are the influence of the variable values used to increase the output voltage generated by the fuel cell from 250V to 600V, as well as the modelling of the two-level DC DC boost converter to get the output voltage as desired is A1= -1.6298 A2= 0.6608 B1= -3.2604 B2=4.0692. Index terms—boost converter, TLBC, system identification, matlab simulink.